2019
DOI: 10.1038/s41380-019-0420-6
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale analyses of the relationship between sex, age and intelligence quotient heterogeneity and cortical morphometry in autism spectrum disorder

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
176
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 159 publications
(216 citation statements)
references
References 96 publications
(146 reference statements)
16
176
3
1
Order By: Relevance
“…Recent work from our group, Bedford et al (2019), and others (Ducharme et al, 2016) mean age = 66.9 ± 6.3, 58 males and 87 females). In addition, a unique contribution of this manuscript is the complementary analyses of microstructure and surface-based morphometry measures of the striatum, globus pallidus, and thalamus in order to achieve a multi-dimensional normative baseline across several indices related to microstructure and morphology.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…Recent work from our group, Bedford et al (2019), and others (Ducharme et al, 2016) mean age = 66.9 ± 6.3, 58 males and 87 females). In addition, a unique contribution of this manuscript is the complementary analyses of microstructure and surface-based morphometry measures of the striatum, globus pallidus, and thalamus in order to achieve a multi-dimensional normative baseline across several indices related to microstructure and morphology.…”
Section: Introductionmentioning
confidence: 58%
“…Furthermore, we sought to examine a potential factor related to the different age trajectories reported in the literature; the effect of quality control (QC) and segmentation accuracy. Recent work from our group, Bedford et al (2019), and others (Ducharme et al, 2016) demonstrate that varying levels of QC alter cortical thickness age trajectories radically. When implementing strict QC criteria, both studies report previously observed higher order trajectories were mostly replaced by linear effects.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Thus, one potential explanation for the male-specific reduction of H in vMPFC could have to do with early developmental and androgen-sensitive upregulation of genes that play central roles in excitatory postsynaptic potentials, and thus ultimately affecting downstream E:I imbalance. Such effects may be sex-differential and thus less critical in human females, serving an important basis of sexdifferential human brain development 43 and explaining the sex-based heterogeneity and qualitative sex differences of autism neurobiology in human 10,44 .…”
Section: Discussionmentioning
confidence: 99%